A commentary on forging a path for CHANGE: culturally focused HIV training for the next generation in pursuit of equity - Jahn Jaramillo; Derrick Forney; Felicia O. Casanova; Naysha N. Shahid; Devina J. Boga; Nequiel Reyes; Renae Schmidt; Sannisha K. Dale; Daniel J. Feaster; Viviana E. Horigian (Critical Public Health)
Training programs focused on developing the next generation of scholars with expertise in HIV and mental health are crucial for advancing health equity and cultivating a diverse workforce by supporting individuals with lived experience and a strong commitment to serving underserved communities. However, disparities persist in the workforce, particularly in the inclusion of professionals typically underrepresented in research. The aim of this commentary is to explore the strengths and challenges of a NIMH-funded training program (T32), Culturally focused HIV Advancements through the Next Generation for Equity (CHANGE), at the University of Miami, with the goal of providing a series of general recommendations. The program excels in leveraging Miami’s unique context, recruiting a cohort of trainees committed to addressing HIV and mental health inequities, delivering a tailored curriculum, and providing strong leadership and mentorship networks to trainees. Additional opportunities for training programs that attract minoritized scholars to realize their vision include further increasing underrepresented scholars in health research, expanding federal funding and institutional investment in training programs, continuing to combat systemic inequities, fostering culturally-sensitive mentorship training, and building upon existing resources to provide trauma-informed support that acknowledges and addresses the unique, intersectional, and historical trauma experienced by trainees. We close with calls to action spanning institutional, community, and policy levels, urging scientists and decision-makers to actively address disparities in diversifying the HIV workforce, fostering equity, and creating inclusive training environments.